Fabrication of Hydro-Pneumatic Crane for Automobiles - P, Nagasankar; P, Tamilselvi; Kumar S, Satheesh; D, Someshwar (International Journal of Engineering and Technology, 2018)
This work applies the fabrication of Hydro pneumatic crane (HPC) which can be used for removing and installing heavy objects such as engines and transmissions from vehicles. The intention of using this project work is to gain knowledge in the field of material handling equipment. This work has dealt with the fabrication of the portable jib crane. The main principle of this project is, the hand pump present in the normal hoist crane is replaced with hydraulic cylinder. The hydraulic piston is coupled with pneumatic pistons, and the hydraulic piston is connected to the boom. The pneumatic cylinder is pumped by air compressor. By calculating rated power of HPC and compared with the existing crane we will prove that the system will work under automated condition without compromising the efficiency of the system.Â